The Funambulist Pamphlets 11: Cinema - Lambert, Léopold (punctum books, 2015)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist, collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema. Volume 11 is devoted to the topic of Cinema: Spike Lee, Béla Tarr, Michelangelo Antonioni and the many other filmmakers named in this volume do not seem to have much in common at first sight; nevertheless, considered through the interpretation of a Spinozist materialist philosophy, their films might have something to say to one another. Take the mud of Red Desert (Antonioni), the volcanic slopes of The Bad Sleep Well (Kurosawa) and the soil of Pina Bausch's Rite of Spring magnified in Pina (Wenders), for example. What these material manifestations have in common is that they are all in relation with bodies, themselves assemblages of moving matter. Similarly, consider Spike Lee's dolly shot, Orson Welles's labyrinth, Béla Tarr's entropy, and Peter Watkins's democratic improvisations: they all manifest the power of immanence and its inexorability. These films involve no deus ex machina; everything in them comes 'from the ground' in a continuous refusal of a celestial or other form of transcendence. Developing this kind of reading of these films allows us to avoid a traditional chronological reading of history of cinema in favor of another, one more dedicated to the philosophical vision of the world that cinema triggers